An Evaluation of MAPIA in Michigan as an Ante-Mortem Supplemental Test for Use in Suspect Tuberculosis Cattle - Scott D. Fitzgerald; Heather A. Grodi; John B. Kaneene (Veterinary Medicine International)
The objective of this study was to make use of bovine tuberculosis suspect cattle from the state of Michigan to validate a multiantigen print immunoassay for use on sera to serve as an improved supplementary ante-mortem test to increase specificity of current tuberculosis testing methods. Over a 27-month period, 234 sera were collected and tested by MAPIA method, which was evaluated using four different interpretation criteria. These results were subsequently compared to final mycobacterial culture and PCR results obtained by the National Veterinary Services Laboratories, Ames, IA, which served as the true indicator of the cattle’s tuberculosis infection status. This study indicates that an interpretation criterion which includes 3 or more positive reactions to the 11 different mycobacteria antigens utilized provided both an acceptable sensitivity (69.39%) and a high specificity (90.27%). This MAPIA technique shows potential for eventual application as a supplementary ante-mortem tuberculosis serologic test following one of the various current or soon-to-be-approved whole herd screening assays as part of a tuberculosis eradication program.